MICROSOFT AZURE - ONE OF THE POSSIBLE WAYS TO VIRTUALIZATION - Milan, KLEMENT (Trends in education, 2016)
At present, virtualization and virtualization technologies represent a powerful tool for the consolidation and simplification of extensive hardware and software structures. Therefore, from the viewpoint of applicability, the potential of virtualization is immense, and virtualization technologies are used in many industries and disciplines. However, their use is connected with considerable investments in the construction of necessary technology background, which may be the reason why the virtualization technologies have not expanded massively in terms of educational institutions yet. The use of virtualization and virtualization technologies at educational institutions appears as very beneficial, and from the perspective of teachers and pupils as challenging. Virtualization can be used not only for running school computer systems, but also for the purposes of the very teaching of pupils and students. Although virtualization would be a very useful tool in students` experiments, unfortunately there are not sufficient funds for building technological facilities, which partly applies to the possibility of its deployment in production, too.Microsoft Azure platform represents one of the ways towards the use of the potential of virtualization technologies at educational institutions at relatively low costs, both for production, and testing or training purposes. The submitted paper describes the possibilities of using this cloud platform and expounds the principle of the actual process of virtualization and virtualization technologies as well as the related typologies of virtualization technologies.
Keywords: virtualization; virtualization tools; desktop virtualization; infrastructure virtualization; cloud virtualization; Microsoft Azure.